1999
DOI: 10.1021/bi982825f
|View full text |Cite
|
Sign up to set email alerts
|

Differences between the Pressure- and Temperature-Induced Denaturation and Aggregation of β-Lactoglobulin A, B, and AB Monitored by FT-IR Spectroscopy and Small-Angle X-ray Scattering

Abstract: We examined the temperature- and pressure-induced unfolding and aggregation of beta-lactoglobulin (beta-Lg) and its genetic variants A and B up to temperatures of 90 degrees C in the pressure range from 1 bar to 10 kbar. To achieve information simultaneously on the secondary, tertiary, and quaternary structures, we have applied Synchrotron small-angle X-ray diffraction and Fourier transform infrared spectroscopy. Upon heating a beta-Lg solution at pH 7.0, the radius of gyration Rg first decreases, indicating a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
110
2
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 187 publications
(137 citation statements)
references
References 56 publications
20
110
2
1
Order By: Relevance
“…Fourier transform infrared spectroscopy has been widely used to probe transitions in secondary conformation of proteins (6,17,31,41), and the use of a diamond anvil cell provides access to secondary structure components of proteins also upon pressurization (31,33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourier transform infrared spectroscopy has been widely used to probe transitions in secondary conformation of proteins (6,17,31,41), and the use of a diamond anvil cell provides access to secondary structure components of proteins also upon pressurization (31,33).…”
Section: Discussionmentioning
confidence: 99%
“…A diamond anvil cell (High Pressure Diamond Optics Inc.) was used for the measurements under pressure. The samples were mixed with powdered ␣-quartz in a stainless-steel compartment (0.5 mm in diameter, 0.05 mm deep) (31,33), and changes in pressure were quantified by the shift of the quartz phonon band at ϳ798 cm Ϫ1 (36). The pressure studies were carried out between 1 bar and ϳ10 kbar.…”
Section: Methodsmentioning
confidence: 99%
“…1) was correlated to the formation of aggregates of this protein. Previous IR studies have shown (48,50,51) that densely packed intermolecular ␤-aggregates give rise to highly characteristic infrared bands. Particularly, a so-called "␤-aggregation band" at 1615 cm Ϫ1 is known to be typical for the presence of these aggregates.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the CD spectrum of the pressurized IAPP sample looks different, with a similar minimum but shifted to about 222 nm, however the overall CD ellipticity has decreased drastically, most likely due to precipitation of the IAPP aggregate (as can be seen by light scattering). In a third step we were looking deeper into the secondary conformational changes using FT-IR spectroscopy, a common tool used for monitoring α-helix to β-sheet transitions and to disentangle between different β-sheet structures that accompany protein aggregation processes [27,33,41], and which can also be used for pressure-dependent spectroscopic studies. Figure 4 shows FT-IR spectra of various IAPP samples: freshly dissolved IAPP and IAPP aggregated for 3 days at ambient pressure and at 3.5 kbar, respectively (all spectra were taken at room temperature, 25 o C).…”
Section: Resultsmentioning
confidence: 99%
“…The temperature in the cell was controlled through an external water-circuit. FT-IR spectroscopy has proven to be a powerful technique to determine the secondary structure elements [17,[27][28][29]. The amide I' band (between 1600 and 1700 cm -1 ) was recorded, which is mainly associated with the carbonyl stretching vibration of the amide groups and which is directly related to the backbone conformation and hydrogen bonding pattern of the protein [29].…”
Section: Methodsmentioning
confidence: 99%